A Research on Tesco's Consumer Purchasing Behavior towards E-Commerce during the Pandemic Period - Utama, A.A. Gde Satia; Verma, Monica; Ng, Jing Yi; Kee, Daisy Mui Hung; Nga, Chun Shuen; Izzati, Nik Nadia; Ng, Yu Xuan; Khoiruwnia, Fadhilah (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2022)
During the pandemic period, people nowadays have two shopping choices, either online or shopping at physical stores. The research was conducted to investigate the impact of the rising of E-commerce during the pandemic period against Tesco consumer purchasing behavior. Three hypotheses are carried out to determine the direction of this research. This research was conducted by having a survey with 100 eligible respondents. Descriptive analysis, regression analysis, and other tests were summarized to determine the relationships of the three hypothesis. The findings indicate that social need, convenience, and business performance have a simultaneous effect on consumer purchasing behavior. Consumer purchasing behavior was statistically associated with convenience and business performance.